Description of Postpartum Mothers’ Characteristics and Knowledge Regarding the Benefits of Postpartum Checkups - Arisandi, Ermawaty; Zalukhu, Elvi Magdalena; S, R. Oktaviance; Sinabariba, Merlina (Universitas Pahlawan Tuanku Tambusai, 2026)
The postpartum period is a critical phase after childbirth that lasts up to 42 days, during which mothers require special attention to recover physically and mentally, as well as to adapt to their new role as mothers. This study aims to describe the characteristics and knowledge of postpartum mothers regarding the benefits of postpartum follow-up visits at the Partner Clinic of Santa Elisabeth School of Health Sciences Medan in 2025. The research employed a descriptive method with a total sampling technique, involving 30 respondents who completed a questionnaire. The results showed that the majority of respondents were aged 20–35 years (90%), had a senior high school education (70%), and worked as farmers (60%). In terms of parity, most respondents were primiparous (53.3%), and regarding the distance from their homes to the healthcare facility, the majority lived less than 3 km away (63.3%). The level of maternal knowledge about the benefits of postpartum follow-up visits was in the “moderate” category for 43.3% of respondents. Conclusion: Based on this study, although most mothers have a moderate level of knowledge, there is still a need to enhance education on the importance of postpartum follow-up visits. Therefore, educational institutions are expected to expand outreach activities by involving students, while healthcare facilities are encouraged to provide specialized educational classes for postpartum mothers and to develop homecare services to support optimal maternal recovery after childbirth